Evaluasi Sistem Pengendalian Intern Persediaan Barang Jadi dalam Meningkatkan Efektivitas dan Efisiensi Operasi Pada PT. Compotec International - Hastoni, Hastoni; Damandari, Sapto Amal; Rachmawati, Sanovi (Jurnal Ilmiah Ranggagading (JIR), 2006)
There are several things emerge in management cycle of finished product stock. They require attention to deal with existing problems by forming companyâs good internal control system. So that conducive climate on one of companyâs assets can be created. Evaluation on internal control system will not merely comprise the process and procedure of management of finished product stock. Itâs also covers data completeness in the form of documents or form linked with stock that must be brought to account in the form of report and reliable accounting data. Keywords: Internal Control, Finished Product Supply